Implications of the post COVID-19 syndrome on mental health in the adult stage (Revista Estudios Psicológicos, 2022)
The long-term effects of the respiratory illness caused by the SARS-CoV-2 virus in the adult population is a situation that generates concern because it alters the physical and mental aspects of the patient to the point of providing an inability in their daily functioning. Therefore, this investigation aims to understand the implications of the post-COVID-19 syndrome on mental health in the adult stage of life. For the methodology structuring, the PRISMA 2020 statement is used, which provides a clear summary of the information on the topic in the study. Among the conclusions, we find that the wide-ranging affectation has consequences at a psychological and psychiatric level, manifested in emotional difficulties in all daily activities, expressed in sadness, low level of spirit and perception of achievements, desmejora the quality of life, affects the state functional, cognition and ability to produce critical disability.
Keywords: adult stage; implications; mental health; post-COVID-19 syndrome